Penerapan Model Problem Based Learning Terhadap Kemampuan Critical Thinking Pada Mata Pelajaran Ekonomi - Sulastri, Fitri; Hermawan, Yoni; Sartika, Sri Hardianti (SJEE (Scientific Journals of Economic Education), 2025)
This study aims to determine the effect of PBL in improving students' critical thinking abilities in the Theory of Money subject. This study was conducted using the Quasi Experimental Design research method in the form of Nonequivalent Control Group Design using pretest and posttest. The data collection technique was in the form of an explanation test on the theory of money material according to the indicators of critical thinking abilities. The results of this study, where the experimental class using the problem based learning model had a difference before and after treatment, the control class using the discovery learning model had an effect before and after treatment, and there was a difference in students' critical thinking abilities between the experimental class and the control class based on the hypothesis test that the Sig. (2-Tailed) value indicates that Ho is rejected and Ha is accepted. Based on the results of the N-Gain test, 77% shows that the application of the problem based learning model is effective in improving students' critical thinking.